The meanings of chimpanzee gestures. - Hobaiter, Catherine; Byrne, Richard W (Curr Biol, 2014)
Chimpanzees' use of gesture was described in the first detailed field study [1, 2], and natural use of specific gestures has been analyzed [3-5]. However, it was systematic work with captive groups that revealed compelling evidence that chimpanzees use gestures to communicate in a flexible, goal-oriented, and intentional fashion [6-8], replicated across all great ape species in captivity [9-17] and chimpanzees in the wild [18, 19]. All of these aspects overlap with human language but are apparently missing in most animal communication systems, including great ape vocalization, where extensive study has produced meager evidence for intentional use ([20], but see [21, 22]). Findings about great ape gestures spurred interest in a potential common ancestral origin with components of human language [23-25]. Of particular interest, given the relevance to language origins, is the question of what chimpanzees intend their gestures to mean; surprisingly, the matter of what the intentional signals are used to achieve has been largely neglected. Here we present the first systematic study of meaning in chimpanzee gestural communication. Individual gestures have specific meanings, independently of signaler identity, and we provide a partial "lexicon"; flexibility is predominantly in the use of multiple gestures for a specific meaning. We distinguish a range of meanings, from simple requests associated with just a few gestures to broader social negotiation associated with a wider range of gesture types. Access to a range of alternatives may increase communicative subtlety during important social negotiations.
Keywords: Animal communication; Animals; Gestures; Pan troglodytes